The provenance and persistence of the perennial Río Loa in the Atacama Desert: links between crustal processes and surface hydrology - Houston, John (Frontiers in Earth Science, 2023)
The Río Loa is a perennial river that crosses the Atacama Desert. A basin-wide survey enables for the first time, the hydrologic regime origin, persistence and processes to be identified. Perennial baseflow in the Ríos Loa and Salado largely originates from intra-arc aquifers which are poorly known. However, the data indicate that despite flood flow being largely confined to the summer (DJF) season, sufficient storage exists in these aquifers to maintain year-round stream flow from high-altitude, across the Atacama Desert to the coast. The intra-arc aquifers of the Western Cordillera receive recharge from time-variable precipitation infiltration and timeinvariant lithospheric inputs. Lithospheric inputs potentially include slab/mantle dehydration, upper crustal melt devolatilization and/or thermally induced upflow of deeply penetrating meteoric water through buried evaporites or carbonates. Downstream, aquifers in the Pre-Andean basins variably interact with surface water, depending on location, river stage and time of year, but they do not supply significant additional sources of baseflow. Hydrochemical processes include those related to volcanic activity, soil carbonate generation, silicate weathering, CO2 degassing and calcite precipitation. Solutes undergo concentration by evaporation, gypsum dissolution, and are further affected by localized NO3, and SO4 inputs and mixing with saline waters. Stable isotopes reveal subcatchment specific precipitation and evaporation, whilst carbon and tritium isotopes are used to analyze recharge sources and processes in the intra-arc aquifers and downstream mixing.